MANAGING ‘BALIGH’ IN FOUR MUSLIM COUNTRIES: Egypt, Tunisia, Pakistan, and Indonesia on the Minimum Age for Marriage - Ropei, Ahmad; Huda, Miftachul; Alijaya, Adudin; Fadhil, Fakhry; Zulfa, Fitria (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
In Islamic law, the concept of baligh has long been debated among clerics. The debate also appears to have resulted in different rules regarding the minimum age of marriage among Muslim countries. This paper aims to reveal the maturity standard regarding the minimum age of marriage in four Muslim countries: Egypt, Pakistan, Tunisia, and Indonesia. This paper is based on library research and employs a comparative study approach. This paper argues that Egypt, Pakistan, Tunisia, and Indonesia have a different minimum age for marriage. In Egypt and Pakistan, the minimum age for marriage is 18 years for men and 16 years for women. However, Pakistan has gone further by instituting legal sanctions if the regulation of the minimum age is violated. In Tunisia, the minimum age for marriage is 18 years for men and women, while in Indonesia it is 19 years for men and women. The determination of the minimum age for marriage is intended for several purposes, including limiting the number of early marriages, reducing the divorce rate, and preparing a strong national generation through the maturity of the marriage age. These interests, from the perspective of Islamic law, are the manifestation of the principle of maslahah (fundamentally aimed at achieving goodness and rejecting harm concerning marital life).[Dalam hukum Islam, konsep balig sudah lama diperdebatkan di kalangan ulama. Perdebatan tersebut juga tampaknya telah menghasilkan aturan yang berbeda mengenai usia minimum pernikahan di antara negara-negara Muslim. Tulisan ini bertujuan untuk mengungkapkan standar kedewasaan mengenai usia minimum menikah di empat negara Muslim: Mesir, Pakistan, Tunisia, dan Indonesia. Makalah ini didasarkan pada penelitian kepustakaan dan menggunakan pendekatan studi komparatif. Tulisan ini berpendapat bahwa Mesir, Pakistan, Tunisia, dan Indonesia memiliki perbedaan usia minimum untuk menikah. Di Mesir dan Pakistan, usia minimum untuk menikah adalah 18 tahun untuk laki-laki dan 16 tahun untuk perempuan. Namun, Pakistan telah melangkah lebih jauh dengan memberikan sanksi hukum jika peraturan usia minimum dilanggar. Di Tunisia, usia minimum untuk menikah adalah 18 tahun untuk pria dan wanita, sedangkan di Indonesia adalah 19 tahun untuk pria dan wanita. Penetapan usia minimal menikah dimaksudkan untuk beberapa tujuan, antara lain membatasi jumlah pernikahan dini, menekan angka perceraian, dan mempersiapkan generasi bangsa yang kuat melalui pendewasaan usia pernikahan. Kepentingan-kepentingan tersebut, dalam perspektif hukum Islam, merupakan manifestasi dari prinsip maslahah (menarik kebaikan dan menolak keburukan dalam kehidupan berumah tangga).]